A tripartite mode of action approach for investigating the impact of aneugens on tubulin polymerization. (4th December 2017) - Stock, Valerie; Sutter, Andreas; Raschke, Marian; Queisser, Nina
Abstract : Chemical‐induced disruption of the cellular microtubule network is one key mechanism of aneugenicity. Since recent data indicate that genotoxic effects of aneugens show nonlinear dose‐response relationships, margins of safety can be derived with the ultimate goal to perform a risk assessment for the support of drug development. Furthermore, microtubule‐interacting compounds are widely used for cancer treatment. While there is a need to support the risk assessment of tubulin‐interacting chemicals using reliable mechanistic assays, no standard assays exist to date in regulatory genotoxicity testing for the distinction of aneugenic mechanisms. Recently reported methods exclusively rely on either biochemical, morphological, or cytometric endpoints. Since data requirements for the diverse fields of application of those assays differ strongly, the use of multiple assays for a correct classification of aneugens is ideal. We here report a tripartite mode of action approach comprising a cell‐free biochemical polymerization assay and the cell‐based methods cellular imaging and flow cytometry. The biochemical assay measures tubulin polymerization over time whereas the two cell‐based assays quantify tubulin polymer mass. We herein show that the flow cytometric method yielded IC50 values for tubulin destabilizers and EC50 values for tubulin stabilizers as well as cell cycle information. In contrast, cellular imaging complemented these findings with characteristic morphological patterns. Biochemical analysis yielded kinetic information on tubulin polymerization. This multiplex approach is able to create holistic effect profiles which can be individually customized to the research question with regard to quality, quantity, usability, and economy. Environ. Mol. Mutagen. 59:188–201, 2018. © 2017 Wiley Periodicals, Inc.